Legal Protection for Foreign Investors in Infrastructure Projects Supporting Mining Downstreaming in Indonesia: A Systematic Literature Review - Sandi Saputra; Sami'an Sami'an; Sarwono Hardjomuljadi; Dwi Edi Wibowo (Journal of Social Research, 2026)
The article aims to identify legal issues and legal solutions that affect legal protection for foreign investment in infrastructure and downstream projects in Indonesia. The analysis uses a systematic literature review method. The focus of the analysis lies in four areas: (1) enforcement of arbitral awards (New York Convention 1958; Law 30/1999), (2) the position of arbitration (seat), lex arbitri, and the standard of "public order", (3) the division of contractual risks in GPBU/EPC/O&M (change-in-law, tax gross-up, step-in lender, termination/compensation, government guarantee, land acquisition), and (4) BIT/ISDS as an additional layer of protection. Although the results show a more pro-enforcement tendency, key problems remain: flexible interpretation of "public order", slow and formalistic exequatur, undisciplined seat selection, inconsistency in clauses in contract documents, inconsistencies in land procurement, and unclear reasons and regressions in government guarantees. This article provides several legal options. The first is a judicial guideline that aims to reduce "public order" and avoid reassessing the subject matter. The second is the standardization of exequatur, which includes standards such as SLAs, file templates, and e-filing. The third is the recognition of short-term relief, which includes an emergency arbitrator. The fourth is the hygienic arbitration clause model, which includes changes in the law, seat, lex arbitri, consolidation, and joinder. The package reduces the risk of greater actions, speeds up the opening of financial accounts, and enhances the legal protection of foreign investors.